Development of technology for the production of all-purpose buckwheat malt using plasmochemically activated aqueous solutions - Kovalova, Olena; Ковальова, Олена Сергіївна; Vasilieva, Natalia; Васильєва, Наталія Костянтинівна; Haliasnyi, I.; Галясний, І. В.; Gavrish, T.; Гавриш, Т. В.; Dikhtyar, A.; Діхтярь, A. М.; Andrieieva, S.; Андрєєва, С. С.; et al. (Technology Center, 2024)
The result of the conducted research is the development of buckwheat malt production technology using plasma-chemically activated aqueous solutions. Buckwheat grain with high starch content became the object of research. The main technological problem is obtaining high-quality brewing malt suitable for the production of gluten-free beer. The expediency of using plasma-chemically activated aqueous solutions as an intensifier of the process of germination of buckwheat grains and an effective disinfectant of buckwheat malt has been experimentally proven. It is shown that the use of plasma chemical activation of technological solutions allows to speed up the process of moistening of buckwheat grain by more than 2 times. The energy and germination capacity of buckwheat grains, when using plasma-chemically activated aqueous solutions, underwent positive changes. The effect of increasing the energy of germination was from 8 to 14 %, and the ability to germinate was 2–9 %. The amylolytic activity of buckwheat malt was analyzed, an increase in amylolytic activity in the range of 30–77 units/g was noted. The extractability of buckwheat malt was investigated separately. This indicator increased by 2–9 % depending on the concentration of peroxides in the solution. The Kolbach number also increased by 2–10 %, which indicates an intensive course of proteolysis. The total amount of amino acids in the experimental samples increased by 619 mg/100 g. There was a significant decrease in the viscosity of the wort, which indicates the high solubility of the obtained buckwheat malt. The technology can be applied in the industrial production of brewing malt and sprouted buckwheat grain of functional purpose. The developed buckwheat malting technology will receive priority in the production of environmentally friendly buckwheat malts of universal purpose that are not contaminated with pathogenic microflora. Результатом проведених досліджень є розробка технології виробництва гречаного солоду з використанням плазмохімічно активованих водних розчинів. Об’єктом досліджень стало зерно гречки з підвищеним вмістом крохмалю. Основною технологічною проблемою є отримання високоякісного пивоварного солоду придатного для виробництва безглютенового пива. Експериментально доведена доцільність використання плазмохімічно активованих водних розчинів, як інтенсифікатора процесу проростання зерна гречки, та дієвого дезінфектанту гречаного солоду. Показано, що застосування плазмохімічної активації технологічних розчинів дозволяє пришвидшити процес зволоження зерна гречки більше ніж в 2 рази. Енергія та здатність проростання у зерна гречки, при використанні плазмохімічно активованих водних розчинів, зазнала позитивних змін. Ефект збільшення енергії проростання склав від 8 до 14 %, а здатності до проростання – 2–9 %. Проаналізовано амілолітичну активність гречаного солоду, відмічено збільшення амілолітичної активності в межах 30–77 од./г. Окремо досліджено екстрактивність гречаного солоду. Цей показник збільшився на 2–9 % в залежності від концентрації пероксидів в розчині. Число Кольбаха також підвищилось на 2–10 %, що свідчить про інтенсивний перебіг протеолізу. Сумарна кількість амінокислот в дослідних зразках збільшилась на 619 мг/100 г. Спостерігається значне зниження в’язкості сусла, що свідчить про високу розчинність отриманого гречаного солоду. Технологія може бути застосована при промисловому виробництві пивоварного солоду і пророщеного гречаного зерна функціонального призначення. Розроблена технологія солодіння гречки отримає пріоритет при виробництві екологічно чистих та не заражених патогенною мікрофлорою гречаних солодів універсального призначення.
Розробка технології виробництва гречаного солоду універсального призначення з використанням плазмохімічно активованих водних розчинів
Keywords: buckwheat malt; гречаний солод; plasma chemical activation; плазмохімічна активація; aqueous solutions; водні розчини; hydrogen peroxide; пероксид водню; amino acids; амінокислоти